Da'wah and Innovation for Economic Empowerment of Traditional Market Traders in The Digital Era - Fauziyah; Nuha, Achmad Arifulin; Mehnaz; Tri Darmaningrum, Khaerunnisa (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
In the current digital era brings many changes to the community, this is also very influential on traditional markets, therefore traditional markets should be one of the economic sectors that require attention and also efforts in community economic empowerment so that da'wah community economic empowerment for traditional market traders is essential in the digital era like today because it affects the continuation of their business. Traditional markets are where direct buying and selling occur between sellers and buyers. Traditional markets have existed since ancient times and are symbols of local people's lives. However, traditional markets have faced significant challenges, and traders must adapt to increasingly sophisticated digital media to compete with modern markets. From this study, the author concludes that da'wah community economic empowerment for traditional market traders is essential in the digital era like today because for the sustainability of their business, by utilizing digital media traders can develop their business and also increase competitiveness and also expand the range of buying and selling, strengthening partnerships between traders and buyers is also a priority in encouraging community economic growth.